Emerging insights into the role of matrix metalloproteases as therapeutic targets in fibrosis - Afratis, N. A.; Selman, M.; Pardo, A.; Sagi, I. (Matrix Biol, 2018)
Fibrosis is the extensive accumulation and buildup of extracellular matrix components, especially fibrillar collagens, during wound healing in response to tissue injury. During all individual stages of fibrosis ECM proteases, mainly matrix metalloproteinases, have diverse roles. The functional role of MMPs and their endogenous inhibitors are differentiated among their family members, and according to the different stages of fibrosis. MMPs levels are elevated in several inflammatory and non-inflammatory fibrotic tissues contributing to the development, progression or resolution of the disease, whereas in other tissues their expression levels can be diminished or be stable to the baseline. The biological roles of MMPs during fibrosis are not fully resolved, but they seem to differ according the specific member of the family, the affected tissue and the stage of the fibrotic response. Remarkably, some members of the family exhibit profibrotic actions while other function as antifibrotic molecules. Diverse animal models indicate that MMPs are contributing in processes related to immunity, tissue repair and ECM turnover, providing significant impact on mechanisms related to fibrosis. For that purpose, these proteases are considered as pharmacological targets and new biological drugs have been developed in order to treat fibrosis.
Keywords: *Extracellular matrix enzymes; *Fibrosis; *matrix metalloproteinases; *Pharmacological targeting; *Up-Regulation; Animals; Disease Progression; Extracellular Matrix/metabolism; Fibrosis/*metabolism; Humans; Matrix Metalloproteinases/*metabolism; Wound Healing